Indian Paradigm of Orthopedic Care in Post-COVID-19 Era - Jeyaraman, Madhan (J Orthop Case Rep, 2021)
Introduction: COVID-19 pandemic caused by the newly emerged strain of coronavirus (SARS-CoV-2) has had phenomenally casted its impact on the health-care systems globally. The rampant spread of contagiosity has challenged the solidarity of the medical fraternity of the developed and developing world. The rising turmoil enforces to trudge with stoicism and expresses the need for planning because of subjugating the prevailing conditions with judicial channelization of available resources. In many developed and developing countries, the resources such as appropriate equipment as well as personnel have been extended to combat the pandemic substantially. At the same time, the populous country such as India has taken a stand to cancel electively planned orthopedic surgeries. However, under the issued guidelines of apex authorities, trauma and emergency services had have been in continuity with a reorganized manner. Hereby, we discuss the present shift in paradigm in the field of orthopedics with an interplay of regenerative orthopedics and telemedicine and its pivotal role against the odds of the COVID-19 pandemic. Besides, we see over the future perspectives and challenges in the purview of resorting to an effective clinical practice in orthopedics specialty. Albeit these guidelines expound strategies to manage trauma and orthopedic cases amidst pandemics but the subsequent post-COVID-19 phase warrants explicable vision and planning. Indeed, resuming elective orthopedics surgical intervention in post-phase of pandemic shall definitively be a task invoking fundamental planning, especially in a resource-limited background. With the rollout of vaccines in the country, the scenario is in favor of returning to normalcy with evaluation for COVID-19 being added to the list of routine medical and surgical screening profiles.